2022
DOI: 10.3389/fnmol.2022.913274
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Theta-Burst Stimulation on Cortical GABA and Glutamate in Treatment-Resistant Depression: A Surface-Based MRSI Analysis Approach

Abstract: Background: Theta burst stimulation (TBS) belongs to one of the biological antidepressant treatment options. When applied bilaterally, excitatory intermittent TBS (iTBS) is commonly targeted to the left and inhibitory continuous TBS (cTBS) to the right dorsolateral prefrontal cortex. TBS was shown to influence neurotransmitter systems, while iTBS is thought to interfere with glutamatergic circuits and cTBS to mediate GABAergic neurotransmission.Objectives: We aimed to expand insights into the therapeutic effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recent studies have also shown that subthreshold iTBS over the L-DLPFC leads to DA release in the striatum using PET (Shaikh, Pellicano et al 2024, Shaikh, Pellicano et al 2024). In a clinical context, suprathreshold iTBS over L-DLPFC increased cortical GABA and Glu in treatment-resistant depression (Spurny-Dworak, Godbersen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that subthreshold iTBS over the L-DLPFC leads to DA release in the striatum using PET (Shaikh, Pellicano et al 2024, Shaikh, Pellicano et al 2024). In a clinical context, suprathreshold iTBS over L-DLPFC increased cortical GABA and Glu in treatment-resistant depression (Spurny-Dworak, Godbersen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Luborzewski et al (2007) noted an elevation in the level of glutamate within the targeted area. Moreover, a recent study by Spurny-Dworak et al (2022) showcased an increase in glutamate transmission also induced by facilitatory TMS (iTBS, intermittent theta-burst stimulation). Importantly, both neurotransmitters are deficient in depression.…”
Section: Rtms-induced Neuroplasticitymentioning
confidence: 98%
“…Neurostimulatory treatments evaluated in TRD include vagus nerve stimulation (VNS), ECT, rTMS, magnetic seizure therapy, deep brain stimulation, and transcranial direct current stimulation [227][228][229][230][231][232][233] .…”
Section: Neurostimulationmentioning
confidence: 99%